2002
DOI: 10.1074/jbc.m202902200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Release of Neurotransmitters from Rat Dorsal Root Ganglia by a Novel Conjugate of a Clostridium botulinumToxin A Endopeptidase Fragment and Erythrina cristagalliLectin

Abstract: Clostridial neurotoxins potently and specifically inhibit neurotransmitter release in defined cell types. Here we report that a catalytically active derivative (termed LH N /A) of the type A neurotoxin from Clostridium botulinum has been coupled to a lectin obtained from Erythrina cristagalli to form a novel conjugate. This conjugate exhibits an in vitro selectivity for nociceptive afferents compared with the anatomically adjacent spinal neurons, as assessed using in vitro primary neuronal culture systems to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 31 publications
2
70
0
1
Order By: Relevance
“…Recently, the ability of a catalytically active derivative of BTX-A to block the secretion from vesicle populations in dorsal root ganglia neuronal cultures has been demonstrated for the release of substance P and glutamate, which are involved in afferent nociceptive transmission to the central nervous system [8]. This evidence supports the clinical application of BTX-A in the treatment of bladder hypersensitive disorders in humans.…”
Section: Introductionmentioning
confidence: 57%
“…Recently, the ability of a catalytically active derivative of BTX-A to block the secretion from vesicle populations in dorsal root ganglia neuronal cultures has been demonstrated for the release of substance P and glutamate, which are involved in afferent nociceptive transmission to the central nervous system [8]. This evidence supports the clinical application of BTX-A in the treatment of bladder hypersensitive disorders in humans.…”
Section: Introductionmentioning
confidence: 57%
“…15 These axons release inflammatory mediators, such as substance P, neurokinin A and CGRP, into peripheral tissues, which exert direct vasoactive effects (vasodilatation and increased vasopermeability) with consequent tissue edema. The block of secretion from vesicle populations in dorsal root ganglia neuronal cultures of substance P and glutamate, as induced by BTX-A, 3 can decrease the effects of neurogenic inflammation. Furthermore, during followup patients did not show any urinary tract infection and the majority did not report any infection at a mean followup of 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of this signal depends on the release of a number of transmitters, including glutamate, substance P and CGRP, from synaptic vesicles. 3 Duggan et al noted that a conjugate obtained by the coupling of a derivative of BTX-A with a lectin shows in vitro selectivity for nociceptive afferents, resulting in the inhibition of neurotransmitters from synaptic vesicles of dorsal root ganglia neuronal cultures. 3 In addition, it was recently reported that intravesical BTX-A significantly decreases afferent nerve mediated contractions to electrical and chemical stimulation in treated rats compared to those in saline treated animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations